Technical results and clinical outcome of transcatheter embolization for severe post-hysterectomy intra-abdominal hemorrhage - Gigi, Anne-Laure; Vanslembrouck, Ragna; Bonne, Lawrence; Timmerman, Dirk; Maleux, Geert (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2025)
To assess the technical and clinical outcome of catheter-directed embolization for severe, post-hysterectomy hemorrhage associated with intra-abdominal hematoma.Retrospective analysis of consecutive patients presenting with severe post-hysterectomy hemorrhage and treated with catheter-directed embolization at the authors’ clinic. Preoperative and follow-up clinical, laboratory, and imaging data were collected from the patients’ electronic medical records.7 patients (mean age 41 years) were included in the study. Indications for hysterectomy were uncontrollable postpartum hemorrhage (n=4), uterine fibroids (n=2), and cervical cancer (n=1). The mean interval between surgery and embolization was 4.7 days. The mean hemoglobin level before embolization was 8.1 g/dL after administration of a mean of 9.6 units of packed cells. The mean volume of the post-hysterectomy abdominal hematoma was 761 ml and angiography revealed a mean number of 2 bleeding arteries per patient. No embolization-related complications were found. Overall, technical and clinical success rates were 85% and 71%, respectively. All patients survived and were discharged after a mean hospital stay of 18 days (range: 4–39 days).Severe, post-hysterectomy hemorrhage associated with large, intra-abdominal hematoma can be safely and effectively managed with catheter-directed embolization. Two or more bleeding arteries may be identified during therapeutic angiography.
Keywords: post-hysterectomy hemorrhage; intra-abdominal hematoma; selective angiography; clinical outcome; bleeding arteries; embolization